Effects of hypoxia on the heart of the juvenile four-finger threadfin (Eleutheronema tetradactylum) based on physiological indicators and transcriptome analysis - Lu, Yi; Amenyogbe, Eric; Yang, Ye-; Wang, Zhong-liang; Jin, Jing-hui; Xie, Rui-tao; Droepenu, Eric Kwabena; Huang, Jian-sheng (Frontiers in Marine Science, 2025)
This study evaluated the effects of hypoxia on the heart of juvenile four-finger threadfin (Eleutheronema tetradactylum) through physiological and transcriptome analysis. Juveniles with an average weight of 122.82 g and length of 24.60 cm were used. Hypoxia significantly increased serum myocardial enzyme activities, including creatine kinase (CK), creatine kinase-MB isoenzyme, lactate dehydrogenase (LDH), and α-hydroxybutyrate dehydrogenase (HDBH). These indicators initially rose and then declined, reflecting cardiac stress and suggesting their potential as early hypoxia biomarkers for real-time aquaculture monitoring. Histological analysis revealed structural damage in myocardial fibers under hypoxia, with increasing severity over time. This underscores the need to minimize oxygen fluctuations to prevent cardiac tissue degeneration. Transcriptome analysis identified upregulated genes involved in cell communication, immune responses, and intracellular signaling, offering potential targets for breeding hypoxia-tolerant species. Kyoto Encyclopedia of Genes and Genomes pathway enrichment analysis highlighted key pathways such as mitogen-activated protein kinase (MAPK), hypoxia-inducible factor-1 (HIF-1), endocytosis, and phagosome formation. The MAPK pathway plays a critical role in cellular stress responses, including survival, proliferation, and apoptosis. Hypoxia-induced activation of MAPKs like ERK, JNK, and p38 regulates stress-responsive genes. HIF-1 signaling regulates oxygen homeostasis, with HIF-1α stabilizing hypoxia-responsive genes such as VEGFA, which promotes vascular remodeling and enhances oxygen delivery. These findings collectively offer practical applications for enhancing aquaculture management, such as monitoring biochemical markers, adopting hypoxia-tolerant breeding, and adjusting environmental conditions to mitigate stress, ensuring better productivity and sustainability. This research provides a foundation for further studies on the molecular mechanisms of hypoxia stress in aquaculture species.